2006
DOI: 10.1597/05-077r.1
|View full text |Cite
|
Sign up to set email alerts
|

Digital Surface Photogrammetry for Anthropometric Analysis of the Cleft Infant Face

Abstract: This study describes preliminary data on the cleft infant facial deformity. The obtained results were mainly in agreement with data in the limited literature. Three-dimensional photogrammetry has proven to be reliable and can be applied more readily to potentially uncooperative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…17 A number of independent studies have demonstrated a high degree of precision and accuracy across a wide variety of 3D surface platforms. 6,18 The safety, speed and reliability of data acquisition that these systems offer are particularly helpful when working with young children, for whom quantification of facial features can be challenging. 9 A number of essential limitations of 3D imaging systems remain a challenge and may hinder their commercial spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A number of independent studies have demonstrated a high degree of precision and accuracy across a wide variety of 3D surface platforms. 6,18 The safety, speed and reliability of data acquisition that these systems offer are particularly helpful when working with young children, for whom quantification of facial features can be challenging. 9 A number of essential limitations of 3D imaging systems remain a challenge and may hinder their commercial spread.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of left-sided cleft is a common finding in most cleft publications, although the aetiology responsible for this predilection is unclear. 19 For this purpose, the digital stereophotogrammetry (3dMD) system was used, which has the main advantages of being noninvasive, having validated accuracy with a mean distance error of 0.04 mm, 18 taking only 0.002 s for image capture, 20 and its submillimeter accuracy. 21 At the level of the eye, the results showed no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The present study's second original feature is the measurement method, in which some lengths were measured along the nasal profile curvature. This measurement differs from those in other morphological studies, where measurements were performed along the straight lines between marking points Ferrario et al, 2003;Kim et al, 2004;Singh et al, 2005;Cho et al, 2006;Krimmel et al, 2006;Duskova et al, 2006a). The authors adopted this original measurement method because the method enabled quantification of subtle differences in nasal curvatures.…”
Section: Originality Of the Authors' Evaluation Methodsmentioning
confidence: 99%
“…The reflection is registered by digital cameras. The laser beam is harmful to the eyes, the relatively long acquisition time (8-30 s) increases the risk of movement artifacts 60 and scanning of the coloured texture of the facial surface can only be done with multiple laser beams, resulting in high costs. The system is very sensitive to light and metal objects, which requires careful control of the environment 44 .…”
Section: Evaluation Of the Different Imaging Techniquesmentioning
confidence: 99%